5x-3-14x-6=0

Simple and best practice solution for 5x-3-14x-6=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-3-14x-6=0 equation:


Simplifying
5x + -3 + -14x + -6 = 0

Reorder the terms:
-3 + -6 + 5x + -14x = 0

Combine like terms: -3 + -6 = -9
-9 + 5x + -14x = 0

Combine like terms: 5x + -14x = -9x
-9 + -9x = 0

Solving
-9 + -9x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '9' to each side of the equation.
-9 + 9 + -9x = 0 + 9

Combine like terms: -9 + 9 = 0
0 + -9x = 0 + 9
-9x = 0 + 9

Combine like terms: 0 + 9 = 9
-9x = 9

Divide each side by '-9'.
x = -1

Simplifying
x = -1

See similar equations:

| y=0.9 | | 4z-18-z+6=0 | | -26-11c=144 | | 8.6-5z=9.6z | | 10x+9-3=9x-4 | | 11x-5=7+12x | | f(x+h)=4x^2+4x+2 | | w^2+10w+21=0 | | 6+x-5-1+6=12 | | 4s^2+28s+49=0 | | 1x^2-5x=0 | | 4y+2x+y+79-x=180 | | 16b^2-9=0 | | 1x^2=-12 | | (2x+1)(2x-5)=0 | | 3(a+15)= | | 20(2x+1)(2x-5)=0 | | 2x+5y=56 | | v^2+12v+27=0 | | 8270=3390-400 | | 0.6n-1.5=0.66 | | x-3=y-2 | | x=1+(1-y) | | 7x=8x-3 | | 2x^3-6x^2-3=0 | | 2x+72=10x-12 | | 176-5x=31x+16 | | 6x+17=12x | | 8x+13=91 | | -(3y+1)-(-2y-4)=-5 | | x^2+4x+76=81 | | 3*-4= |

Equations solver categories